Effect of Functionalized Graphene Oxide (FGO) on the Electrical and Dielectrical Properties of PVA Films - Sundus H. Merza (Journal of Global Pharma Technology, 2019)
In the present work, nanocomposite of poly (vinyl alcohol) (PVA) incorporated with functionalized graphene oxide (FGO) were fabricated using casting method. PVA was dispersed by varying content of FGO (0.3, 0.5, 0.8, 1 wt %). The PVA- FGO nanocomposite was characterized by FT‐IR, FE-SEM and XRD. Frequency dependence of real permittivity (ε’), imaginary (ε’’) and a.c conductivity of PVA/FGO and PVA/GO nanocomposite were studied in the frequency range 100 Hz- 1 MHz. The experimental results showed that the values of real (ε’) and imaginary permittivity (ε’’) increased dramatically by increasing the FGO content in PVA matrix. PVA/ FGO (1 wt %) nanocomposite revealed higher electrical conductivity of 6.4×10-4 Sm-1 compared to 1.4×10-8 Sm-1 for PVA/GOKeywords: Dielectric spectroscopy, Functionalized Graphene oxide, Nanocomposite, PVA, Maxwell-Wagner-Sillars polarization.